Faktor Sukses dalam Pengembangan Wisata Pedesaan - I Wayan Wiwin (UHN IGB Sugriwa Denpasar, 2019)
One of the most popular rural development strategies is tourism with a variety of entrepreneurial opportunities that arise, this can generate foreign exchange and employment as well as the growth of small industries. The purpose of writing this article is to identify the factors that have helped rural communities successfully develop tourism and entrepreneurial opportunities. Some of the results of research conducted in several tourist villages in Bali, such as Penglipuran Village in Bangli, Padangtegal Village in Ubud, Sangeh Village in Badung, and Kukuh Village (Alas Kedaton) in Tabanan, the results clearly show how important community approaches are in developing rural tourism and entrepreneurship, they cannot work without the participation and collaboration of local communities, local governments and tourism businesses, both directly and indirectly involved in tourism.